2015
DOI: 10.3390/w7051959
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Toxicological Evaluation of the River Danube Using in Vitro Bioassays

Abstract: Abstract:The Joint Danube Survey 3, carried out in 2013 was the world's biggest river research expedition of its kind. The course of the second largest river of Europe passes large cities like Vienna, Budapest and Belgrade and is fed from many tributaries like Inn, Thisza, Drava, Prut, Siret and Argeș. During the 6 weeks of shipping the 2375 km downstream the River Danube from Germany to the Black Sea an enormous number of water samples were analyzed and collected. A wide spectrum of scientific disciplines coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We have assumed that the assay would provide preliminary screening of genotoxic potential, but the induction ratio has not exceeded value 1.5 (threshold value) in any of the investigated samples. Similarly, in the study of Kittinger et al [ 30 ] performed on the water samples of the Danube River, only four sites out of 68 investigated within the JDS3 showed mutagenic potential, indicating either to low sensitivity of the assay or low genotoxic potential of water.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We have assumed that the assay would provide preliminary screening of genotoxic potential, but the induction ratio has not exceeded value 1.5 (threshold value) in any of the investigated samples. Similarly, in the study of Kittinger et al [ 30 ] performed on the water samples of the Danube River, only four sites out of 68 investigated within the JDS3 showed mutagenic potential, indicating either to low sensitivity of the assay or low genotoxic potential of water.…”
Section: Discussionmentioning
confidence: 77%
“…When constructing the battery of bioassays we were focused on types of assays which have already been employed earlier in ecogenotoxicological studies of the Sava River [ 8 14 , 27 ]. Also, we have used experience gained during the Joint Danube Survey 3 –JDS3 [ 22 , 28 , 29 , 30 ] for updating the assay list as usage of the same methodology would enable comparison of water quality of the Sava and Danube in further research. As the assays employed in the study showed different sensitivity in detection of the stressors at investigated sites we have finally employed IBR approach to identify the most critical spots on the river but also to recommend which site has potential to be a reference site for Sava River.…”
Section: Discussionmentioning
confidence: 99%
“…Although most samples did have a response in the assays, the effects were relatively low, with the EC values for the oxidative stress and AhR assays similar to previously benchmarked EC values for surface water . Kittinger et al also only detected minimal effects in Danube River samples when assessing genotoxicity. Furthermore, ER activation, when expressed as BEQ bio (0.02–1.1 pM), was lower than generally observed in wastewater effluent due to dilution in the river, although one contaminated site, JDS 41 (BEQ bio 4.7 pM), was identified by this assay.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, Brack et al ( 2019 ) suggested EBMs that would allow for detecting the combined effects of mixtures. This suggestion in fact, had been done in New Zealand, Australia, and Canada (Brunner et al 2020 ; Kittinger et al 2015 ).…”
Section: Compound Mixtures In Watermentioning
confidence: 80%